O diálogo entre aspectos da cultura científica com as culturas infantis na educação infantil - Fagionato-Ruffino, Sandra (2012)
This research is the result of concerns about different ways of thinking and approaching the natural sciences in early childhood education. Assumes that before children go to school already have contact with the scientific aspects of the mass media, by the contact with parents and other adults or bigger children, or even by the direct contact with elements and phenomena related to natural sciences. Likewise, these aspects are present in early childhood education institution, in some cases lending the discipline form and how it is used to educate in elementary school. In this sense, this study aims to identify children in interaction with pairs, with adults and everything that surrounds them, their actions, perceptions and ways of meaning from the natural world and technological pondering how to insert elements of scientific culture in the space of childhood , without stacking it to children. We sought to identify the elements or natural phenomena and technological perceived or handled by children, to know the social and cultural experiences for the scientific culture that children share with other children and adults and to analyze the characteristics of the experiences triggered by the merger of practices related to scientific culture within early childhood education. Childhood is understood as a social category and children as social actors, members of this category and producing crops. The qualitative research was based on studies of childhood and the ideas of Humberto Maturana on autopoiesis, cognition, language and emotion. The interest was mainly focused on the experiences of children in free play and activities directed by the teacher who was also the researcher. Analysis of data obtained by means of video recording, photo, logbook of the researcher and children s drawings, led to the conclusion that the experience of children with aspects of scientific culture, they give different names to the same thing, create forms of expressions to explain what they think, think with different logics, between reality and fantasy; have different ideas on the same element or phenomenon arising from their previous experiences with influences like family, religion, television and the observation of nature. The commitment to their ideas seems to be less important than the affective interests and their pair s comments trigger argument, reformulation of the previous explanation or the incorporation of new elements. In the act of children's investigating the most important is the interaction itself, not an explanation of what is observed. Their actions do not go towards the assimilation of procedures and explanations, but of creation. In this sense, it is important to consider the scientific knowledge as one more among many others that comes from other areas of experience, without characterizing it as absolute truths.